Reliability assessment of the post-limit stiffness and ductility of steel joints - Gervásio, Helena (2004)
Steel joints must exhibit sufficient ductility for safe structural behaviour. This is especially true for partial-strength steel joints, whereby the nonlinear response of the joint plays an important part in the overall response of the structure. Uncertainty in joint response, particularly beyond the elastic limit of the moment-rotation curve, naturally leads to a probabilistic treatment of the ductility of steel joints. It is the objective of the present paper to compare a direct probabilistic approach with simulation techniques using the Monte-Carlo method both at the component and joint level, in the context of the component method, with the aim of establishing safe limits for the ductile behaviour of the steel joints.